Analisis Gaya Kepemimpinan Kepala Desa dalam Pembagunan Desa Suak Puntong Raya Kabupaten Nagan Raya - Hendri Hendri; Agatha Debby Reiza Macella (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The government of Gampong Suak Puntong is led by a keuchik or so-called Gampong leader and assisted by other Gampong government officials. Keuchik Gampong Suak Puntong as the head of government has the main role and responsibility to realize this development. It is hoped that the keuchik will be able to become the main driver to improve village development and community welfare. The formulation of the problem in this study is the first problem of unresponsive communication or lack of concern from the community to be involved in the village development process. Second, the problem of a static government system as a result of the long power transfer process as a result of the resignation of the keuchik in 2016. Third, the unstable socio-economic problems of the community due to the covid-19 pandemic, so that many Gampong funds have been diverted to solve problems. In this study the researchers used qualitative methods, with approaches to observations, interviews, documentation, and used secondary data sources such as literature, journals, and other media in explaining activities or facts in the research area that can assist in collecting data in the research area this research.